Affective medievalism : love, abjection and discontent - Prendergast, Thomas A. (Thomas Augustine); Trigg, Stephanie (Manchester medieval literature and culture, 2019)
This work argues that the temporal privilege of the medieval masks the extent to which the medieval and medievalistic are mutually constitutive and ultimately dependent not on absolutist epistemological claims but on how feelings and temperaments affect the way we approach the Middle Ages.